PEDAGOGICAL PREREQUISITE FOR THE FORMATION OF ATTITUDES TOWARDS CHILDHOOD IN CHILDREN OF A PRESCHOOL EDUCATIONAL ORGANIZATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In this article we can learn about such concepts as the formation of a friendly attitude of a preschool organization to children, their deeper assimilation of the concepts of friendship.